2010
DOI: 10.1093/bioinformatics/btq245
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning based prediction for peptide drift times in ion mobility spectrometry

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…In fact, there are only three individual studies which have reported over 1,000 CCS values and thus would be considered large-scale surveys, 54,55,72 underscoring the fact that the reporting of quantitative ion mobility measurements is predominantly an interlaboratory initiative.…”
Section: Significant Ccs Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there are only three individual studies which have reported over 1,000 CCS values and thus would be considered large-scale surveys, 54,55,72 underscoring the fact that the reporting of quantitative ion mobility measurements is predominantly an interlaboratory initiative.…”
Section: Significant Ccs Contributionsmentioning
confidence: 99%
“…The large blue bubble in Figure 7 corresponds to the 8676 peptide cross sections published by Smith and coworkers in 2010 in support of developing theoretical methods for predicting the IM drift time based upon the primary amino acid sequence. 72 While most of the CCS values have been for tryptic peptides, there is recent and significant efforts being made in the quantitative IM analysis of structurally-interesting peptide and protein classes, including helical peptides, 174176 metalloproteins, 177180 intrinsically-disordered proteins, 181184 metamorphic proteins, 185,186 amyloids, 187194 and membrane-bound proteins and assemblies. 117,195198 The last three years has seen a balance of cross section reporting across most of the chemical classes, including lipids and carbohydrates.…”
Section: Ccs Coverage Over Timementioning
confidence: 99%
“…PLSR differs from machine learning classifiers based on Bayes' theorem or support vector machines (Merkwirth et al, 2004;Arimoto et al, 2005) in that it can be used to reconstruct a continuous range of predicted values for the variable of interest, rather than simply binning it into one of two or more categories. Compared with support vector regression, PLSR is easier to implement and interpret, and it often provides similar results (Ustün et al, 2007;Shah et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 IM-MS is a particularly useful analytical combination in that the mass spectrometry separates molecules based on their intrinsic mass, whereas ion mobility provides a complimentary separation based on molecular size and shape based on the gas-phase collision cross section (CCS). While there has been significant progress in correlating the CCS to the primary molecular structure and composition, 2325 it is challenging to predict CCS particularly for isomeric systems. Consequently, the ability of IM-MS to separate any given isomeric system is difficult to predict without referring to empirical studies.…”
mentioning
confidence: 99%